2016
DOI: 10.1016/j.transproceed.2016.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Evaluation of Geographically Distant vs Geographically Nearby Living Kidney Donors

Abstract: Background Living donor kidney transplant (LDKT) can be impeded by multiple barriers. One possible barrier to LDKT is a large physical distance between the living donor's home residence and the procuring transplant center. Methods We performed a retrospective, single-center study of U.S. living kidney donors who were geographically distant (residing ≥150 miles) from our transplant center. Each distant donor was matched to four geographically nearby donors (<150 miles from our center) as controls. Results F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
(16 reference statements)
0
8
0
1
Order By: Relevance
“…In addition, our study adjusted for donor candidate distance to transplant center given that time and distance of travel to the center may be a contributing factor to the rate of progression through the living donor evaluation process . Unlike previous literature, we were able to demonstrate that a substantial proportion of AA donor candidates lived within 50 miles of our transplant facility . Thus, delays may be a manifestation of the transplant candidate's social network; drawn predominantly from biological relatives, persons living in close proximity, and from persons who are likely to be deemed medically ineligible for live kidney donation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, our study adjusted for donor candidate distance to transplant center given that time and distance of travel to the center may be a contributing factor to the rate of progression through the living donor evaluation process . Unlike previous literature, we were able to demonstrate that a substantial proportion of AA donor candidates lived within 50 miles of our transplant facility . Thus, delays may be a manifestation of the transplant candidate's social network; drawn predominantly from biological relatives, persons living in close proximity, and from persons who are likely to be deemed medically ineligible for live kidney donation.…”
Section: Discussionmentioning
confidence: 81%
“…27 Unlike previous literature, we were able to demonstrate that a substantial proportion of AA donor candidates lived within 50 miles of our transplant facility. 28 Among those who did not make it to the next step, the median time from referral to medical screening was 3.4 mo (2.6 mo AA vs 3.7 mo non-AA), from medical screening to evaluation was 3.9 mo (5.3 mo AA vs 3.4 mo non-AA), from evaluation to clearance was 2.9 mo (4.5 mo AA vs 2.7 mo non-AA), and from clearance to transplant was 3.3 mo (3.0 mo AA vs 3.7 mo non-AA)…”
Section: Discussionmentioning
confidence: 99%
“…Living kidney donors (LKDs) currently provide nearly one third of the organs for kidney transplants in the United States, but the number of living kidney donations has been decreasing since 2004. 1 Studies have identified multiple potential barriers to living kidney donation, including completing the evaluation process, 2 concern about health risks, [3][4][5][6][7] geographic distance from the transplant center, 8 and donation-related financial concerns. [9][10][11][12] Donation-related financial concerns have received increased attention, given the potential for intervention, with a 2015 consensus statement from the American Society of Transplantation calling for the reduction of financial barriers to living donor kidney transplantation (LDKT) and the achievement of financial neutrality for LKDs.…”
Section: Introductionmentioning
confidence: 99%
“…Common evaluation times included the time until approval to donate, donation, or rejection, although the definition of the starting point varied (Table 3 ). 35 , 47 , 48 , 65 , 72 The time until donation ranged from 4 to 14 months across studies and transplant programs. One report described a single recipient who received a kidney from her father (before) and her mother (after) the living donor evaluation process was redesigned to be completed in 1 day.…”
Section: Resultsmentioning
confidence: 99%